Linear, two- and four-armed pyridine-decorated thiazolo[5, 4-d]thiazole fluorophores: Synthesis, photophysical study and computational investigation. (December 2022) - Jouaiti, Abdelaziz; Giuso, Valerio; Cebrián, Cristina; Mercandelli, Pierluigi; Mauro, Matteo
Abstract: A novel family of thiazolo[5, 4- d ]thiazole (TzTz) fluorophores having a general formula (py)n -π-TzTz-π-(py)n ( n = 1 or 2, py = pyridine) is herein reported. The investigated compounds are decorated with alkoxy-substituted pyridine scaffolds bearing chains with different lengths (a = methoxy, b = 2-ethylhexan-1-oxy, c = 2-decyltetradecan-1-oxy) that are connected at either the para - or meta -position(s) of the phenyl bridging ring. The compounds feature either a linear ( n = 1, para -substituted, series 8 ), two-armed ( n = 1, meta -substituted series 9 ) or four-armed ( n = 2, meta -substituted series 10 ) molecular architecture. Steady-state and time-resolved photophysical investigation is employed to characterize the optical properties of the compounds in both diluted CH2 Cl2 and CH2 Cl2 :trifluoroacetic acid (TFA) 95:5 solutions, as well as in thin-film in poly (methyl methacrylate) (PMMA) matrix at 20 wt% doping. All compounds display electronic transitions with mainly π-π* nature at both solution and solid state. However, while both peripheral pyridyl-phenyl moieties and the π- TzTz- π core participate in the absorption transitions, the emission involves mostly the π- TzTz- π core. A clear effect of the positional isomerism on the photophysical properties is observed, with the protonation of the peripheral pyridines offering a further modulation. Thus, these results provide some useful hints on the molecular design of TzTz-based compounds as promising photoactive materials. Graphical abstract: A novel family of near-UV to bluish-green emitting thiazolo[5, 4- d ]thiazole chromophores is presented and their optical properties investigated by jointly photophysical and computational techniques. Image 1 Highlights: Nine novel thiazolo[5, 4- d ]thiazole fluorophores with peripheral pyridines is presented. The compounds possess either a linear, two- or four-armed molecular structure. All the compounds display good near-UV to bluish-green fluorescence. Linear derivatives show better photoluminescence quantum yields compared to non-linear counterparts up to 0.42. The nature of the short-lived excited state is confidentially described as π-π*.